PENGARUH TINGKAT PENGANGGURAN DAN ZAKAT TERHADAP PERTUMBUHAN EKONOMI PADA NEGARA ASEAN TAHUN 2014-2023 - Fitri Rahmadhani; Sri Rahma; Agustina Mutia (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2026)
Economic development is a long-term process capita income and significant changes in economic structure. To achieve this, a country requires an optimal resource and service management system to create economic stability and sustainability. However, challenges such as growth instability, unemployment, and inflation remain obstacles, especially with the global recession expected in 2023. This study aims to analyze the effect of unemployment and zakat on economic growth in three ASEAN countries (Indonesia, Malaysia, and Singapore), selected purposively based on their improved zakat management regulations. The method used is panel data regression analysis with secondary data for the period 2014- 2023. The results show that partially, unemployment has a negative but insignificant effect, while zakat has a negative and significant effect on economic growth. Simultaneously, both variables influence economic growth in ASEAN countries